Behavioral phenotype in Costello syndrome with atypical mutation: A case report. Issue 1 (4th November 2014) - Alfieri, Paolo; Caciolo, Cristina; Piccini, Giorgia; D'Elia, Lidia; Valeri, Giovanni; Menghini, Deny; Tartaglia, Marco; Digilio, Maria Cristina; Dallapiccola, Bruno; Vicari, Stefano
Abstract : Costello syndrome (CS) is a rare genetic disorder caused, in the majority of cases, by germline missense HRAS mutations affecting Gly 12 promoting enhanced signaling through the MAPK and PI3K‐AKT signaling cascades. In general, the cognitive profile in CS is characterized by intellectual disability ranging from mild to severe impairment. The first published descriptions of behavior in CS children underlined the presence of irritability and shyness at younger ages with sociable personality and good empathic skills after 4–5 years of age, however some recent studies have reported autistic traits. We report on a 7‐year‐old boy heterozygous for a rare duplication of codon 37 (p.E37dup) in HRAS, manifesting impaired social interaction and non‐verbal communication and with circumscribed interests. These additional features improve phenotype delineation in individuals with rare HRAS mutations, facilitating the development of specific behavioral treatments which could lead to improvement in cases of autism spectrum disorder. © 2014 Wiley Periodicals, Inc.